1994
DOI: 10.1109/49.329333
|View full text |Cite
|
Sign up to set email alerts
|

A caching strategy to reduce network impacts of PCS

Abstract: We propose an auxiliary strategy, called per-user caching, for locating users who move from place to place while using Personal Communications Services (PCS). The caching strategy augments the basic location strategy proposed in existing standards such as GSM and IS-41, with the objective of reducing network signaling and database loads in exchange for increased CPU processing and memory costs. Since technology trends are driving the latter costs down, the auxiliary strategy will become increasingly attractive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0
4

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(104 citation statements)
references
References 10 publications
2
98
0
4
Order By: Relevance
“…In this section, we shall parametrize our model based on the optimal hexagonal structure determined in [8] and the PCS network shown in Figure 1 as discussed in [9]. Our result enhances the previous results in [8,9] in that we allow the optimal number of forwarding steps to be determined if the forwarding and resetting technique is to be used in tracking mobile users under the same mobile environment structure and setting.…”
Section: Hexagonal Coverage Modelsupporting
confidence: 56%
See 1 more Smart Citation
“…In this section, we shall parametrize our model based on the optimal hexagonal structure determined in [8] and the PCS network shown in Figure 1 as discussed in [9]. Our result enhances the previous results in [8,9] in that we allow the optimal number of forwarding steps to be determined if the forwarding and resetting technique is to be used in tracking mobile users under the same mobile environment structure and setting.…”
Section: Hexagonal Coverage Modelsupporting
confidence: 56%
“…Of course, during the time period in which the pointer connection is set up, call requests can still arrive. Figure 1 shows a PCS network as discussed in [9]. Here, the home location register (HLR) and visitor location registers (VLRs) contain databases for tracking mobile users, but the intermediate switches such as regional signal transfer points (RSTPs) and local signal transfer points (LSTPs) are only used for connecting the HLR with VLRs.…”
Section: System Descriptionmentioning
confidence: 99%
“…Thus, no explicit deregistration messages are needed so as to reduce the communication cost [18]. Figure 1 illustrates a possible hierarchical PCS network as discussed in [13]. The HLR and VLRs each contain a database for location management.…”
Section: Degradable Location Managementmentioning
confidence: 99%
“…Therefore the goal is to minimize the total cost incurred in servicing location-update and calldelivery operations. For the two-tier HLR-VLR architecture, it has been separately reported that when the frequency of incoming calls is higher than the mobile user's mobility, that is when the call-to-mobility ratio (CMR) is high, the location cache scheme [13] is effective, while when CMR is low the forwarding and resetting algorithm (FRA) [14,15], the paging and location update algorithm (PLA) [16] and the local anchor algorithm (LAA) [17] are effective. There is no systematic way to categorize these location management algorithms and to compare their performance characteristics [8].…”
Section: Introductionmentioning
confidence: 99%
“…Decentralized hash indexing [15,16,26]. Decentralized hash indexing has been proposed for resource discovery in peer-to-peer networks.…”
Section: Existing Work and Our Design Rationalementioning
confidence: 99%